Agronomic efficiency and productivity of transplanted kharif rice (Oryza sativa) as influenced by fertilizer briquettes - KALITA, SONTARA; DAS, DHRITISMITA; KURMI, KHAGEN; GOGOI, BHABESH; DAS, RANJAN; CHAUHAN, MANOJ KUMAR; PATHAK, KALYAN (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during rainy (kharif) season of 2022 at the research farm of Assam Agricultural University, Jorhat, Assam to evaluate the effect of fertilizer briquettes on growth and productivity of transplanted rice. The field experiment was laid out in RBD comprising of 13 treatments, replicated thrice. Growth of rice, panicles/m2 and yield were subjected to significant variation under different fertilizer management practices. Higher plant height, tillers/ m2, panicles/m2, yield and agronomic efficiency were recorded under FDP, 120% RDN + 100% P and K + ZnSO4 @10 kg/ha + biofertilizer (T12). This might be owing to reduced losses of nutrients and efficient uptake by plants compared to broadcasted method of fertilizer application where most of the applied fertilizers were susceptible to various losses availing lesser amount of nutrients for crop uptake.